2010
DOI: 10.1134/s1063773710010044
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of peculiarities of the stellar velocity field in the solar neighborhood

Abstract: Based on a new version of the Hipparcos catalogue and an updated Geneva-Copenhagen survey of F and G dwarfs, we analyze the space velocity field of ≈17000 single stars in the solar neighborhood. The main known clumps, streams, and branches (Pleiades, Hyades, Sirius, Coma Berenices, Hercules, Wolf 630-αCeti, and Arcturus) have been identified using various approaches. The evolution of the space velocity field for F and G dwarfs has been traced as a function of the stellar age. We have managed to confirm the exi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 50 publications
2
23
0
Order By: Relevance
“…The probability that the star HIP 74033 belongs to the KFR08 stream is 0.65 according to Bobylev et al (2010). Since the location of this star in velocity space is also close to the Arcturus stream, we are not surprised that it was selected as a potential member of the Arcturus stream in Arifyanto & Fuchs (2006).…”
Section: Is the Kfr08 Stream A Dissolved Cluster?mentioning
confidence: 99%
See 4 more Smart Citations
“…The probability that the star HIP 74033 belongs to the KFR08 stream is 0.65 according to Bobylev et al (2010). Since the location of this star in velocity space is also close to the Arcturus stream, we are not surprised that it was selected as a potential member of the Arcturus stream in Arifyanto & Fuchs (2006).…”
Section: Is the Kfr08 Stream A Dissolved Cluster?mentioning
confidence: 99%
“…Stellar sample Bobylev et al (2010) found nineteen stars that probably are members of the KFR08 stream. Seventeen of those are high-probability members.…”
Section: Observationsmentioning
confidence: 99%
See 3 more Smart Citations